Green finance and energy efficiency improvement: The role of green innovation and industrial upgrading - Peijia Wang; Xuelu Xu (Innovation and Green Development)
The emergence of green finance plays a pivotal part in propelling the transition towards sustainable energy and the advancement of environmentally conscious economic development. In this comprehensive study, data from 30 Chinese provinces spanning the period 2010 to 2020 is used to examine the connection between eco-friendly finance and the enhancement of energy efficiency. The findings indicate that energy efficiency is greatly supported by green finance. Green innovation significantly contributes to enhancing energy efficiency, while industrial upgrading is not the pathway through which green finance achieves these improvements. Meanwhile, it is evident that there exists regional disparity in the impact of eco-friendly finance on the augmentation of utilization efficiency of energy, with a more pronounced effectiveness observed in provinces located within the regions located in the central and western parts of the nation. Based on the thorough analysis conducted herein, this paper strongly advocates for the persistent development and widespread enactment of policies related to green finance.